FILM DOKUMENTER GEROMBOLAN PEMBURU BATU MENGGANA (Mengapresiasi Tinggalan Leluhur Dengan Talenta) - Hari Suryanto (President University, 2018)
Gerombolan Pemburu Batu (Stone Hunters) is a community who appreciates the remains of valueson historical sites in many regions. The community uses Talents as a form of creativity to reproduce the talentsin the form of creative products. These marginal sites—locations unknown to many people—has become maininterest for impromptu visits. These visits offer the opportunity to learn cultural literacy in a fun way.